How do you simplify the expression (5x-2)^2?
2 Answers
Explanation:
To solve this problem first you rewrite as follows:
Then you proceed to FOIL it:
Where you multiply the
Now you multiply the
Now combine them:
Simplify:
Explanation:
"express " (5x-2)^2" as " (5x-2)(5x-2)
"each term in the second bracket is multiplied by each term in"
"the first bracket"
(color(red)(5x-2))(5x-2)
=color(red)(5x)(5x-2)color(red)(-2)(5x-2)
=(color(red)(5x)xx5x)+(color(red)(5x)xx-2)+(color(red)(-2)xx5x)+(color(red)(-2)xx-2)
=25x^2+(-10x)+(-10x)+4
=25x^2-10x-10x+4
=25x^2-20x+4